Primary monosymptomatic nocturnal enuresis and associated factors in a referral continence clinic of Abu Dhabi - Salvatore Arena; Mario Patricolo (PAGEPress Publications, 2017)
The aim of the present study was to investigate the prevalence of primary monosymptomatic nocturnal enuresis (PMNE) and its associated factors in a major referral centre for nocturnal enuresis in the City of Abu Dhabi. Children referred to the Pediatric Continence Clinic of Department of Pediatric and Urology Surgery at Al Noor Hospital, Abu Dhabi (UAE), between January 2014 and January 2016 for the suspected diagnosis of NE were considered. The inclusion criteria of our study were: age 5-14 years; full medical history and physical examination; urine dipstick to exclude glycosuria and proteinuria; completion of diagnostic urological work-up; final diagnosis of PMNE. Parents were encouraged to follow a program on urotherapy. All children underwent renal and bladder ultrasound, abdominal X-ray and uroflowmetry with electromyography. Constipation was treated, if present. 39 patients had a diagnosis of PMNE. A constipation was present in 17 children (43.6%). Statistical analysis documented a higher incidence of PMNE in the male groups. 38 out of 39 children (97.4%) resolved PMNE, 14 following urotherapy and 24 required medical therapy with desmopressin. Our experience clearly confirms a higher prevalence rate of PMNE in boys than in girls. In the study population, the large intake of dry and reducedin- fibers foods, the excessive intake of carbonated drinks and the hot climatic condition might negatively influence the incidence of fecal retention and the subsequent PMNE. A multi-modal assessment seems to be effective in the management of PMNE, showing a very high rate of resolution.